Effects of Quercetin on Blood Pressure: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials. Issue 7 (July 2016) - Serban, Maria‐Corina; Sahebkar, Amirhossein; Zanchetti, Alberto; Mikhailidis, Dimitri P.; Howard, George; Antal, Diana; Andrica, Florina; Ahmed, Ali; Aronow, Wilbert S.; Muntner, Paul; Lip, Gregory Y. H.; Graham, Ian; et al.
Abstract : Background: Quercetin, the most abundant dietary flavonol, has antioxidant effects in cardiovascular disease, but the evidence regarding its effects on blood pressure (BP) has not been conclusive. We assessed the impact of quercetin on BP through a systematic review and meta‐analysis of available randomized controlled trials. Methods and Results: We searched PUBMED, Cochrane Library, Scopus, and EMBASE up to January 31, 2015 to identify placebo‐controlled randomized controlled trials investigating the effect of quercetin on BP. Meta‐analysis was performed using either a fixed‐effects or random‐effect model according to I 2 statistic. Effect size was expressed as weighted mean difference (WMD) and 95% CI. Overall, the impact of quercetin on BP was reported in 7 trials comprising 9 treatment arms (587 patients). The results of the meta‐analysis showed significant reductions both in systolic BP (WMD: −3.04 mm Hg, 95% CI: −5.75, −0.33, P =0.028) and diastolic BP (WMD: −2.63 mm Hg, 95% CI: −3.26, −2.01, P <0.001) following supplementation with quercetin. When the studies were categorized according to the quercetin dose, there was a significant systolic BP and diastolic BP‐reducing effect in randomized controlled trials with doses ≥500 mg/day (WMD: −4.45 mm Hg, 95% CI: −7.70, −1.21, P =0.007 and −2.98 mm Hg, 95% CI: −3.64, −2.31, P <0.001, respectively), and lack of a significant effect for doses <500 mg/day (WMD: −1.59 mm Hg, 95% CI: −4.44, 1.25, P =0.273 and −0.24 mm Hg, 95% CI: −2.00, 1.52, P =0.788, respectively), but indirect comparison tests failed to significant differences between doses. Conclusions: The results of the meta‐analysis showed a statistically significant effect of quercetin supplementation in the reduction of BP, possibly limited to, or greater with dosages of >500 mg/day. Further studies are necessary to investigate the clinical relevance of these results and the possibility of quercetin application as an add‐on to antihypertensive therapy.